Indonesian Life Expectancy: Role of Health Infrastructure and Socio-Economic Status - Endri Kristanto; Akhmad Daerobi; Bhimo Rizky Samudro (Signifikan: Jurnal Ilmu Ekonomi, 2019)
The purpose of this study is to analyze the role of health infrastructure and public socio-economic status on life expectancy in Indonesia. Health infrastructure indicators are health personnel, health facilities, and health insurance. Meanwhile, socio-economics indicators are dependency ratio, income inequality, and poverty. The models are estimated using a panel data set for 34 provinces in Indonesia from 2010 to 2016. This research is using a fixed-effect panel data approach. Empirical results show that health personnel and health insurance have a positive relationship with life expectancy. Dependency ratios and poverty also show a negative relationship with life expectancy. On the other hand, the availability of health facilities and income inequality have a weak relationship with life expectancy. This empirical examination result will help Indonesian governments to improve several aspects in order to increase life expectancy in Indonesia